2023
DOI: 10.1097/paf.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Thyroid Storm in the Setting of Untreated Graves Disease and Use of the Synthetic Cannabinoid MDMB-4en-PINACA

Abstract: Thyroid storm, or thyrotoxic crisis, is a rare but well-described and potentially lethal exacerbation of thyrotoxicosis, characterized by multisystem effects due to failure of the hypothalamic-pituitary-thyroid axis. Thyroid storm is seen most frequently in the setting of inadequately treated Graves disease; however, it may also be triggered or exacerbated by infection, trauma, childbirth, radioiodine treatment, and pharmacologic agents. While there are rare reports of cases in which illicit drug use may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…However, there is no information on its concentrations or any postmortem findings. Ricciardo reported a case of finding MDMB-4en-PINACA in a case of fatal thyroid storm, but they were not able to quantify the MDMB-4-en-PINACA due to prior embalming [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no information on its concentrations or any postmortem findings. Ricciardo reported a case of finding MDMB-4en-PINACA in a case of fatal thyroid storm, but they were not able to quantify the MDMB-4-en-PINACA due to prior embalming [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two patients experienced acute respiratory distress despite medical efforts and expired [46,121]. One patient died of MOF within hours of resuscitation of three cardiac arrests after complete heart block [239]. Chao et al reported the death of two male patients: one patient died due to MOF while on ECMO and one due to CS [59].…”
Section: (B) Non-pharmacological Therapymentioning
confidence: 99%